The Analysis of Barriers in Succession Processes of Family Business with the Use of Grey Incidence Analysis (Polish Perspective) - Więcek-Janka Ewa; Mierzwiak Rafał; Kijewska, Joanna (Naše gospodarstvo/Our economy, 2016)
The article presents results of research on the identification and evaluation of barriers faced by successors in family businesses during the first process of succession. The analysis of empirical material used grey systems theory, which was considered as an equivalent for the analysis of small samples and qualitative research. While conducting the literature review and empirical study, the authors concentrated on (a) the identification of barriers in the development of family firms and (b) eliciting the perspective of the new generation of owners in family firms entering the succession process through an empirical analysis of the assessed level of risk in relationships with family and business.